2003
DOI: 10.1521/suli.33.2.211.22769
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Training and the Treatment of Suicidal Clients: The Students' Perspective

Abstract: Existing literature suggests that graduate programs may not provide adequate training in working with suicidal clients. Therefore, we surveyed 238 predoctoral psychology interns and assessed the prevalence of clients engaging in suicidal behaviors and the amount of formal training in managing suicidal clients received. Results showed approximately 5% of participants indicated a client suicide and 99% indicated they had treated at least one suicidal client during their graduate training. In contrast, results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 13 publications
(26 reference statements)
4
55
0
Order By: Relevance
“…Furthermore, residency training directors from various medical schools have also acknowledged inadequacies in their training programs (Sudak et al 2007). Our study supports the educational gaps reported by Dexter-Mazza and Freeman (2003); Ellis et al (1998);Schmitz et al (2012);Sudak et al (2007). To some extent, only the field of psychiatry seems to be attempting to ensure that their trainees are equipped with the skills required for assessing and managing suicidal patients (Schmitz et al 2012).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, residency training directors from various medical schools have also acknowledged inadequacies in their training programs (Sudak et al 2007). Our study supports the educational gaps reported by Dexter-Mazza and Freeman (2003); Ellis et al (1998);Schmitz et al (2012);Sudak et al (2007). To some extent, only the field of psychiatry seems to be attempting to ensure that their trainees are equipped with the skills required for assessing and managing suicidal patients (Schmitz et al 2012).…”
Section: Discussionsupporting
confidence: 86%
“…This is a systematic problem in healthcare education and training. For example, Dexter-Mazza and Freeman (2003) found that only half of the psychology interns received formal training in assessing and managing suicidal patients whereas only 25 % of social workers and 6 % of counselors have training in suicide assessment (Schmitz et al 2012). Additionally, a survey of program directors reported that most of the training occurred in passive formats and only one quarter of the programs offer suicide prevention training via skill development workshops (Ellis et al1998).…”
Section: Discussionmentioning
confidence: 99%
“…Accreditation demands often overshadow programs' ability to cover critical content such as death and dying issues. Research suggests limited death and dying content in counseling (Offer, Granello, & Wheaton, 2012), clinical psychology (Dexter-Mazza & Freeman, 2003), and school psychology (Seadler, 2000).…”
Section: Service-learning Graduate Education Counselor Preparationmentioning
confidence: 99%
“…Although narrow examinations have been conducted in fields such as counseling (Offer et al, 2012) and clinical psychology (Dexter-Mazza & Freeman, 2003; only related to suicide), a comprehensive and simultaneous assessment of offerings across many service provision disciplines (e.g., social work, rehabilitation counseling, counseling psychology) is warranted. In addition, such research needs to be conducted using an international lens, as has been done on a limited basis within nursing and medicine (e.g., Downe-Wamboldt & Tamlyn, 1997).…”
Section: Implications For Researchmentioning
confidence: 99%
“…In one study of over 200 pre-doctoral psychology interns, findings indicate that only 50% of the sample reported being formally trained in managing such situations through their academic training programs (Dexter-Mazza & Freeman, 2003). This is a concerning estimate for clinical supervisors, considering that supervisees practice under a clinical supervisor's license, leaving a tremendous burden of responsibility on supervisors' shoulders.…”
Section: Introductionmentioning
confidence: 99%